Hero of two worlds : the Marquis de Lafayette and the Age of Revolution - Duncan, Mike, 1980- (New York : PublicAffairs, 2021)
"Few in history can match the breadth and depth of the revolutionary career of the Marquis de Lafayette. Over fifty incredible years at the heart of the Age of Revolution, he fought as one with righteous revolutionaries on both sides of the Atlantic. As an idealistic and courageous teenager serving in the American Revolution, he used his considerable wealth and savvy to help the Americans defeat the British. Then he returned home, and was a principal player in the French Revolution. And in his final act, at seventy years old, he was instrumental in the dramatic overthrow of the Bourbon Dynasty during the Revolution of 1830. All the while, he never wavered from the principles he had written into the Declaration of the Rights of Man in 1789: That men are born and remain free and equal, deserving of liberty, property, safety, freedom of speech, and the ability to resist oppression. Through this age of revolutionary upheaval, Lafayette remained unshakably committed to the principles he had outlined. From the time that he was an enthusiastic 19-year-old to the time he was a world-weary 74-year-old, his resolve never wavered. As the saying goes, if we don't learn from history, we are doomed to repeat it. The contemporary relevance and the life and times of the Marquis de Lafayette have never been more relevant. Today, the values codified and practiced by Lafayette are increasingly taken for granted and our society has grown complacent about their supposedly immutable and permanent force. His life is thus the story of where we came from-and what we stand to lose if we abandon the ideals for which he fought"--
Includes bibliographical references and index.
HB
Keywords: Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834.; France. -- Armée -- Biography; Generals -- France -- Biography; Generals -- United States -- Biography; Statesmen -- France -- Biography; United States -- History -- Revolution, 1775-1783 -- Biography; United States -- History -- Revolution, 1775-1783 -- Participation, French; France -- History -- Revolution, 1789-1799.